(untitled) (Research, Society and Development, 2021)
The search for built environments with better air conditioning for the user is a growing interest in civil construction, in addition to guaranteeing a watertight environment, without infiltration and being able to provide environments with milder temperatures. In this sense, the objective of this work was to evaluate whether the use of waterproofing PVC coating improves thermal comfort in buildings. The tests were carried out at laboratory and field conditions, evaluating the temperature variation on the faces of tiles with and without waterproofing PVC coating. In the laboratory, surface temperatures were evaluated under the incidence of light from a reflector. In the field, direct sunlight was measured. The results showed that the use of PVC coating acts as a waterproofing agent, and as reflector of solar radiation, providing a difference between the external and internal temperature in the tile of about 20°C. The use of waterproofing PVC coating for thermal improvement in buildings is effective, resulting in the reflection of part of the solar radiation incident on the covering surface of buildings, hindering the passage of heat to the internal area.